The effect of Lactobacillus acidophilus and Lactobacillus casei on the in vitro bioaccessibility of flaxseed lignans (Linum usitatissimum L.). Issue 4 (9th April 2018) - Muñoz, O.; Fuentealba, C.; Ampuero, D.; Figuerola, F.; Estévez, A. M.
Abstract : L. casei slightly improves the bioaccessibility of SDG for whole flaxseed digestion. Abstract : Secoisolariciresinol (SECO) is present in flaxseeds as a glucoside, secoisolariciresinol diglucoside (SDG), which can be metabolized to enterodiol (ED) and enterolactone (EL) by the human intestinal microbiota. The aim of this study was to evaluate the effect of Lactobacillus casei and Lactobacillus acidophilus on the bioaccessibility of flaxseed lignans from a complete in vitro digestion of whole flaxseeds (WFs) and flaxseed flour (FF). Lignans are only detected in the large intestine. The bioaccessibility of SDG for FF digestion can be ordered as follows: control (without probiotics) > L. casei > L. acidophilus ; and for WF digestion, only in the presence of L. casei SDG was detected. For SECO and EL, the presence of both probiotics had no effect on FF and WF digestion. However, in the digestion of WF both L. casei and L. acidophilus increased ED bioaccessibility in the first 12 h; but both probiotics had no significant effect on FF digestion.